European beech reproduction is not reduced by drought, including the 2003, 2018, and 2022 extremes - Jakub Szymkowiak; Michał Bogdziewicz; Dave Kelly; Jessie Foest; Sabine Braun; Burkhard Beudert; Francesco Chianucci; Andrea Cutini; Rachel Gaulton; Georg Gratzer; Angelika Kölbl; Georges Kunstler; et al. (Proceedings of the National Academy of Sciences, 2026)
Climate change is intensifying drought stress in temperate forests, but its effects on tree reproduction, central to forest regeneration and migration capability, remain poorly understood. Here, we analyze 221 time series of beech ( Fagus sylvatica ) seed production across Europe to test whether drought reduces seed output. We isolate drought exposure during the flowering, pollination, and seed maturation phases of reproduction, and test for legacy effects on future reproduction. Seed production was not impaired by summer drought, and dry spring conditions were associated with increased output, likely via enhanced pollen dispersal. Thus, once initiated, beech reproduction is not reduced by drought, with no suppression of reproduction the following year. Reproduction was not reduced at the driest sites during exceptional European summer droughts in 2003, 2018, and 2022. Considered alongside prior evidence that drought suppresses forest growth and elevates mortality, these findings indicate that vital rates can respond in opposite directions to the same stressor. Such contrasts may sustain forest reproduction during heat–drought events yet shift demographic balance toward higher mortality and turnover as climatic extremes intensify.